Penerapan Inaportnet dalam Proses Pelayanan Penyandaran Kapal: Studi Kasus - Rizqi Aini; Intan Sianturi; Faris Nofandi (Politeknik Ilmu Pelayaran Semarang, 2021)
The significance of ports in global trade activities has a significant impact on a city, region, and even a nation. A port with adequate facilities and a superior system will make port activities more effective, neutral, and even simple for its users. Inaportnet is a facility that is currently used by major Indonesian ports, including the port of Tanjung Emas in Semarang. The users of this system include exporters, importers, shipping lines, and others, in addition to port players. PT Global Logistic Agency is one of the user companies that has been using the Inaportnet framework. This study was descriptive research using a structured interview method. This study aims to examine the use of Inaportnet from the side of the organizer represented by PT. Global Logistics Agency. The results showed that the use of Inaportnet played an important role in the implementation of ship berthing services in terms of time efficiency, energy, and demurrage, the Inaportnet system is still found down or system errors are due to maintenance from the management unit so that PT. Global Logistic Agency must carry out conventional or manual implementation.